The Trickle-Down Effect of Leaders’ VWGB on Employees’ Pro-Environmental Behaviors: A Moderated Mediation Model - Wu, Jianfei; Zhang, Weinan; Peng, Chuanhu; Li, Juan; Zhang, Saiyu; Cai, Wenjing; Chen, Dan (Frontiers in Psychology, 2021)
Although previous research has highlighted the positive effect of leaders’ voluntary workplace green behavior (VWGB), limited research attention has been paid to empirically test how and when the trickle-down effect of such behavior can exist. Taking a role model perspective and drawing on social identity theory, this research aims to fill the gap by proposing and testing the mechanism and boundary conditions of the influencing processes whereby leaders’ VWGB can trickle down to employees’ pro-environmental behaviors. Through theorizing a moderated mediation model, the current research empirically examines the hypotheses via conducting a hierarchical regression analysis. We employed a survey questionnaire research design to collect two-wave and multi-source data. The data used in the analysis are from survey responses of 313 subordinate-supervisor dyads at two different time points. The results show that leaders’ VWGB can have a trickle-down influence on employees’ task-related pro-environmental behavior and proactive pro-environmental behavior through their green self-identity and that this trickle-down effect is greater among employees with higher green climate perceptions. Our results reveal the intervening mechanism and boundary condition of leaders’ VWGB via conducting a systematic examination on how the effect trickles down.